ON NEW EXACT SPECIAL SOLUTIONS OF THE GNLS(m, n, p, q) EQUATIONS - İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2010)
In this paper, we establish exact special solutions of the generalized nonlinear Schrodinger equation with nonlinear dispersion (called the GNLS(m, n, p, q) equation) by using a sn-cn method. Some new Jacobi elliptic, envelope compacton and solitary pattern solutions of GNLS(m, n, p, q) equations are obtained.
Keywords: Generalized nonlinear Schrodinger equation; compacton solution; soliton; sn-cn method